Use of Emerging Technologies in Learning Punjabi Language (ShodhVarta, 2022)
The total number of languages spoken in the world are 7100 and in India there are 1652 mother tongues and 19500 sub-dialects. According to the 8th schedule of India, the number of recognized languages is 22 and Punjabi language is 1 of them.  After COVID-19 in India, the usefulness of mobile phone learning is increasing continuously. Use of Technology Enabled Learning (TEL) is increasing the learning capacity.  Use of (TEL) is being promoted as per NEP 2020. Keeping the above in mind, Learn Punjabi App has been prepared using the following. PHP and MySQL were used as the backend and HTML, CSS and JavaScript were used for the front end for the website and apps designed in Flutter. The e-content offered through this digital platform is created by experts giving everyone a chance to learn from the best teachers. The range of teaching-learning has been expanded outside the classroom.